Estimated inpatient malnutrition prevalence, screening tool utilization, and dietitian referral rates across hospitals during extension of phase 2 of More-2-Eat - Yingying Xu; Rachel A. Warren; Shirley M. Peters; Sonya Boudreau; Tina N. Strickland; Mari Somerville; Brenda L. MacDonald; Heather Keller; Leah E. Cahill (Clinical Nutrition Open Science)
Summary: Background & Aims: Malnutrition is associated with increased hospital length of stay, disease burden, and healthcare costs. The Integrated Nutrition Pathway for Acute Care (INPAC) is a validated multi-step algorithm that includes screening using the Canadian Nutrition Screening Tool (CNST) and diagnosis using Subjective Global Assessment (SGA). This study aims to understand (1) the prevalence of inpatient nutrition screening completion, (2) the proportion of at-risk inpatients referred to dietitians, and (3) the malnutrition prevalence among a sample of hospital inpatients. Methods: In 2021, INPAC was implemented in five hospital wards across Nova Scotia (NS) as an extension of More-2-Eat NS Study. As part of the implementation, hospital chart audits (n=672) were completed from 2021-2022 to gather data on malnutrition screening, dietitian referral, and nutrition assessment. Statistical analysis involved chi-square, Kruskal Wallis, and t-tests. Results: Nutrition screening at admission occurred for 54.9% of audited patients, with variation among sites (p<0.001). 34.5% of these screened patients were at nutritional risk, of whom 79.8% were referred to a dietitian. 14.4% of all charts audited had a malnutrition diagnosis as per SGA, as did 28.5% of patients screened by the CNST. 94.2% of patients who underwent SGA were diagnosed with malnutrition. Conclusion: Inpatient malnutrition is prevalent in NS hospitals but under-diagnosed due to gaps in screening. INPAC implementation increased dietitian referrals, SGA, and malnutrition diagnosis. Investigation is needed to assess and overcome barriers to screening, consequences to clinician workload, and the burden of malnutrition on prognosis and hospital stay.